Hubungan antara Religiusitas dan Adversitas dengan Adaptabilitas Karier Siswa SMK - Firdaus, Naufal Rifqi; Muslihati, Muslihati; Apriani, Rizka (Buletin Konseling Inovatif, 2025)
This study aimed to determine the partial and simultaneous relationship between religiosity and adversity on the career adaptability of students in vocational high schools. This study used a correlational descriptive approach with a total sample of 138 students. The sampling technique used a proportional random sampling technique. The instruments used were the religiosity, adversity, and career adaptability scales. Research data were analyzed using descriptive analysis, assumption test, multiple regression test, and hypothesis testing. The research results show that; (1) most students have moderate levels of religiosity, adversity, and career adaptability; (2) there is a partial and simultaneous positive relationship between religiosity and adversity variables on the career adaptability of vocational high school students.